The laminated wood boatbuilder a step-by-step guide for the backyard builder - Miller, Hub (International Marine, 1993)
"Hub Miller's drawings are encyclopedic. Every significant stick, fastening, shadow, and process is revealed with clean, expressive lines in black on white"